Implementasi Sistem Payment Gateway Midtrans Pada Fitur Pembelian Robux Website Bloxstore.id dengan Metode Prototyping (International Forum of Researchers and Lecturers, 2025)
This study explores the implementation of the Midtrans payment gateway system on the Bloxstore.id website using the Prototyping method. The main objective is to enhance the website's payment transaction process by integrating an efficient and secure payment gateway. The Prototyping method was chosen for its iterative approach, which allows for continuous feedback and system refinement. This research demonstrates how the integration of Midtrans improves the user experience by streamlining the payment process and offering various payment options. The results indicate significant improvements in transaction speed, security, and user satisfaction. This study’s findings are valuable for e-commerce platforms looking to optimize their payment systems and build customer trust through secure and efficient transaction methods.